Ọ̀rọ̀ Lẹyẹ ń Gbọ́! A Deserving Tribute to Alàgbà Adébáyọ̀Mosọbalájé Ajíbádé Àkàndé Fálétí (Ọdẹ Àdàbà) - Félix Ayoh’Omidire (Yoruba Studies Review, 2021)
The Institute of Cultural Studies is today celebrating in grand style the life and arts of Late Alàgbà Adébáyọ̀ Mosobalaje Ajibade Akande Fálétí (1921- 2017). This grand gesture is a testimony of the importance of Bàbá Fálétí and the great value this University community attached and continues to attach to the passage of this great man through our Citadel of Learning. On the whole, Adébáyọ Fálétí was recognized as a singular man of culture ̀ whose imprints in the sand of the Yorùbá cultural terrain have forever become indelible, thanks to his intense dedication to the promotion of the Yorùbá “ọmọlúàbí” cultural ethos and the use of his God-given talents to promote Yorùbá history, poetry, orature, cinema and the Arts in general.